Factors Affecting Behavioural Intention of Online Food Delivery Service Consumers in Kathmandu Valley - Pokhrel, Laxman; Shah, Rinku (Journal of Business and Social Sciences Research, 2022)
The paper aims to investigate the factors influencing behavioural intention of online food delivery services in the Kathmandu Valley. The paper applied a cross-sectional survey research design with structured questionnaires. The data were collected from 277 respondents. The Covariance-Based Structural Equation Model (CB-SEM) was used to test hypotheses. The behavioural intention of online food delivery services is positively influenced by performance expectancy, social influence, and facilitating conditions. However, effort expectancy has no significant influence on behaviour intention for online food delivery services. In this paper, the researcher and manager will gain theoretical and managerial insights. This is among the few studies that investigate the factors influencing online food delivery services by applying the unified theory of acceptance and use of technology (UTAUT) in the Nepalese context.